Calcific tendinopathy: an unexpected side effect of tyrosine kinase inhibitor?. Issue 13 (10th November 2022) - Canon, Alice; Roy, Lydia; Chevalier, Xavier; Giraudier, Stéphane; Eymard, Florent
Abstract: Musculoskeletal (MSK) pains have been reported during TKI treatment or after its discontinuation in patients with chronic myeloid leukemia (CML). We hypothesized that MSK pains originate from calcific tendinopathy according to preliminary clinical observations. We conducted a retrospective study including CML patients divided into three groups: patients with MSK pain during TKI treatment; asymptomatic patients during TKI treatment; patients with MSK pain after TKI discontinuation. Patients with MSK pain were clinically evaluated, and the presence of calcific deposits was assessed in X-rays of both shoulders and pelvis. Forty-five patients were included; 14 described MSK pain during TKI treatment and 12 after TKI discontinuation. A diagnosis of rotator cuff tendinopathy was retained for 57.7% of patients and of gluteus tendinopathy in 19.2%. The prevalence of calcifications in shoulders and/or hips was 64.3% in symptomatic patients receiving TKIs, 63.2% in asymptomatic patients and 75.0% in patients with MSK pain after TKI treatment.